Dynamics of nitrogen and xenon plasma streams generated by MPC device - Chebotarev, V.V.; Garkusha, I.E.; Ladygina, M.S.; Marchenko, A.K.; Petrov, Yu.V.; Solyakov, D.G.; Tsarenko, A.V.; Tereshin, V.I.; Trubchaninov, S.A.; Yelisyeyev, D.V.; Hassanein, A. (Вопросы атомной науки и техники, 2007)
Magnetoplasma compressor (MPC) of compact geometry is developed for generation of dense plasma streams of different working gases. Discharge characteristics and parameters of the plasma streams, generated by MPC in different modes of operation are investigated. Dynamics of compression zone formation and energy efficiency of MPC are analyzed. Створено магніто-плазмовий компресор (МПК) компактної геометрії для генерації густих плазмових потоків різних газів. Досліджено характеристики розрядів і параметри плазмових потоків, що генеруються МПК у різних режимах роботи. Проаналізовано динаміку формування зони компресії й енергетичну ефективність МПК. Создан магнито-плазменный компрессор (МПК) компактной геометрии для генерации плотных плазменных потоков различных газов. Исследованы характеристики разрядов и параметры плазменных потоков, генерируемых МПК в различных режимах работы. Проанализированы динамика формирования зоны компрессии и энергетическая эффективность МПК.